Food security and technological solutions in military settings: a bibliometric and thematic analysis - Razali, Mohamad Azli; Md Radzi, Elias; Tazijan, Farina Nozakiah; Rahmatullah Khan, Hussin Khan; Din, Norrina; Rezo, Khairul Hidayat; Zainol, Noorliza (Universiti Teknologi MARA, Sabah, 2025)
Food security and technology have become increasingly important in military contexts, especially as global events such as the COVID-19 pandemic and geopolitical conflicts highlight vulnerabilities in food supply chains. This study aims to explore the intersection of food security technologies within military operations through a bibliometric and thematic analysis. Conducting a bibliometric analysis provides a structured view of research trends, identifying key authors, influential journals, and emerging themes, ensuring the study’s focus and relevance. The study used Scopus and Web of Science databases to gather publications, with data analyzed using tools like ScientoPy and VOSviewer for visualization. The bibliometric analysis focused on examining global research output, leading countries, and technological advancements in food security, while the thematic analysis employed Braun and Clarke’s (2006) six-step framework to identify recurring themes and patterns. Key findings indicate a surge in publications on food security in military contexts from 2019 to 2024, driven largely by technological innovations such as the Internet of Things (IoT) and artificial intelligence (AI). The analysis also revealed that the United States and China lead in research output, while emerging research themes focus on global food security, the environmental impact of military food systems, and the role of technology in enhancing operational readiness. This study contributes valuable insights into how technological advancements are shaping the future of food security in military operations, offering guidance for future research and policymaking in high-risk environments.